Development and validation of a nomogram to predict cancer-specific survival in patients with hypopharyngeal squamous cell carcinoma treated with primary surgery. Issue 12 (December 2021) - Wang, Ke; Xu, Xia; Xiao, Ruotao; Du, Danyi; Wang, Luqi; Zhang, Hanqing; Lv, Zehong; Li, Xiangping; Li, Gang
Objective: We aimed to develop a nomogram to predict cancer-specific survival (CSS) in patients with hypopharyngeal squamous cell carcinoma (HSCC) treated with primary surgery to provide more accurate risk stratification for patients. Methods: We retrospectively collected data of 1144 eligible patients with HSCC from the Surveillance, Epidemiology, and End Results (SEER) database between 2004 and 2015. Patients were randomly divided into training and validation groups (ratio 6:4) and we used univariate and multivariate Cox analysis. We developed and validated a nomogram using calibration plots and time-dependent receiver operating characteristic, Kaplan–Meier, and decision curves. Results: Age; marital status; T, N, and M stage; and postoperative adjuvant therapy were independent factors associated with CSS, which were included in the nomogram. The nomogram's C-index was 0.705 to 0.723 in the training group and 0.681 to 0.736 in the validation group, which were significantly higher than conventional American Joint Committee on Cancer (AJCC) staging. Calibration curves showed good agreement between prediction and observation in both groups. Kaplan–Meier and decision curves suggested the nomogram had better risk stratification and net benefit than conventional AJCC staging. Conclusions: We established a nomogram that was superior to conventional AJCC staging in predicting CSS for HSCC.